2021
DOI: 10.5799/jmid.951506
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rifampicin-resistant Tuberculosis in Pediatric Patients by GeneXpert MTB/RIF

Abstract: Objectives: India has the largest burden of MDR-TB worldwide, with an annual incidence of 1,30 000 patients. Multidrug-resistant tuberculosis (MDR-TB) carries a poor prognosis, a high mortality rate, and treatment success rates as low as 65%. The mortality in India is estimated to be about 480,000 per year. The aim of the study was to evaluate Rifampicin-resistant Tuberculosis and its distribution by GeneXpert in a tertiary care hospital. Methods: A total of 2864 samples were processed from the patients attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
2
Order By: Relevance
“…Overall, this study's MTB and rifampicin-resistant TB frequency was 18.98% and 7.11%, respectively. The incidence rate of M. tuberculosis (18.33%) in this study was higher than the previous study that reported 6.5% [18] and 7.9% [19] in Ethiopia, 13.8% [20] in Nepal, and 12% [21] in India. The incidence rate of M. tuberculosis infection among total suspects (n = 39,107) tested for GeneXpert MTB/RIF was 18.98% (7156/37,695), which is lower than the previous study that reported 38.77% [22] in China, 22.65% [23] and 22.9% [24] in Nigeria, and 23.82% [25] in India.…”
Section: Discussioncontrasting
confidence: 89%
“…Overall, this study's MTB and rifampicin-resistant TB frequency was 18.98% and 7.11%, respectively. The incidence rate of M. tuberculosis (18.33%) in this study was higher than the previous study that reported 6.5% [18] and 7.9% [19] in Ethiopia, 13.8% [20] in Nepal, and 12% [21] in India. The incidence rate of M. tuberculosis infection among total suspects (n = 39,107) tested for GeneXpert MTB/RIF was 18.98% (7156/37,695), which is lower than the previous study that reported 38.77% [22] in China, 22.65% [23] and 22.9% [24] in Nigeria, and 23.82% [25] in India.…”
Section: Discussioncontrasting
confidence: 89%
“…Overall, this study's MTB and Rifampicin Resistant TB frequency was 18.33% and 7.11%, respectively. The incidence rate of M. tuberculosis (18.33%) in this study was higher than the previous study reported 6.5% [14] and 7.9% [15] in Ethiopia, 13.8% [16] in Nepal, and 12% [17] in India. The incidence rate of M. tuberculosis infection among total suspects (n=39107) tested for Xpert MTB/RIF was 18.33% (7156/39107), which is lower than the previous study reported 38.77% [18] in China, 22.65 % [19], 22.9% [20] in Nigeria and 23.82% [21] in India.…”
Section: Discussioncontrasting
confidence: 85%
“…7 Acid-fast bacilli have a beaded look and are bright red. 13 The specimen was inoculated with the culture medium and allowed to grow at 37°C for 4 weeks. 6…”
Section: Smear Microscopy and Culturementioning
confidence: 99%
“…7 The systems documented the presence or absence of M. tuberculosis after two hours, classifying the bacterial load as very low, low, medium, or high as well as the subject's susceptibility to the antibiotic rifampicin. 13 We obtained the values of sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) by using the formulas mentioned as follows:…”
Section: Genexpert Mycobacterium Tuberculosis/resistance To Rifampinmentioning
confidence: 99%